Litchi flower essential oil balanced lipid metabolism through the regulation of DAF-2/IIS, MDT-15/SBP-1, and MDT-15/NHR-49 pathway - Chen, Yun; Qin, Qiao; Luo, Jingrui; Dong, Yusi; Lin, Chunxiu; Chen, Houbin; Cao, Yong; Chen, Yunjiao; Su, Zuanxian (Frontiers in Nutrition, 2022)
Lots of litchi flowers are discarded in China every year, while litchi flower is rich in volatile compounds and exhibits strong anti-obesity activity. The LFEO (litchi flower essential oil) was extracted by the CPTD (continuous phase transformation device) independently developed by our research group to recycle the precious material resources in litchi flowers. However, it’s fat-reducing effect and mechanism remain unclear. Here, employing Caenorhabditis elegans as a model, we found that LFEO significantly reduced the fat storge and TG content in normal, glucose-feeding, and high fat conditions. Second, LFEO remarkably reduced body width in worms, and evidently decreased both size and number of lipid droplets in ZXW618. Meanwhile, LFEO treatment didn’t affect energy intake, but increase its energy consumption via enhancing average speed in worms. Further, LFEO might balance the worms’ fat metabolism through regulating DAF-2/IIS pathway, sbp-1/mdt-15 pathway, and nhr-49/mdt-15 pathway. Moreover, LFEO might inhibit the expression of acs-2 gene through nhr-49 to reduce the β-oxidation activity. Our study presented new insights into the role of LFEO in alleviating fat accumulation and provided references for the large-scale production of LFEO to promote the development of the litchi circular economy.